Implementation of Law No. 6 Year 2011 on Immigration Against Abuse of Visit Visa on Arrival at Immigration Office Class I TPI Denpasar - Ni Putu Glory Damayanti; Ni Putu Anik Prabawati (Westscience Press, 2024)
The purpose of the research is to know and understand the implementation of Law No. 6 of 2011 concerning immigration against the abuse of visit visa on arrival at the Immigration Office Class I TPI Denpasar, from the initial problem, namely the existence of foreigners who come to Indonesia, especially Bali, because Bali is a province that one of them is in demand by foreigners, so there are not a few foreigners who come to Bali. However, with this, it does not rule out the possibility of abuse committed by foreigners, one of which is to abuse a visit visa on arrival. The informant in this research is one of the officers from the Immigration Intelligence and Enforcement Section (Inteldakim). This type of research uses qualitative with the type of case study. Data collection techniques using observation, interview and documentation methods. Based on the findings of this study, it shows that the maximum has been achieved which can be seen from the aspects of communication indicators, resources, disposition, and bureaucratic structure that have been carried out appropriately and well.